Hakikat Ilmu Pengetahuan Sosial: Strategi memahami dan perbaikan kesalahan konsep - Kurniawan, Ganda Febri (JIPSINDO, 2022)
Penelitian bertujuan untuk merumuskan strategi memahami hakikat IPS bagi calon guru. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan mengedepankan relevansi tema artikel terdahulu sebagai dasar koleksi data. Analisis data dilakukan dengan teknik analisis data interaktif. Hasil penelitian menunjukan bahwa sangat mungkin seorang Sarjana Pendidikan IPS dapat memahami hakikat IPS saat masa studi apabila sistem belajar IPS dapat mengedepankan penekanan pada konsep integrated dan mengikuti tradisi IPS yang ada. Diskusi sebagai langkah demokratis perlu dikedepankan untuk menyadarkan peserta didik tentang pentingnya belajar IPS, sehingga pemahaman yang dibangun bukan sekedar normatif, tetapi yang diharapkan adalah bersifat kritis. Pemahaman yang dibangun dilandaskan pada keinginan bertanya dan mengetahui, bukan informasi searah yang diberikan oleh pengajar ataupun buku teks. Sudah saatnya bidang studi IPS lebih terbuka dan demokratis dalam membentuk karakter guru yang memahami hakikat IPS dalam mendukung pembangunan sumber daya manusia nasional yang sedang dilakukan.The nature of Social Sciences: Strategy to understanding and revised on concept falseThis study aims to formulate strategies to understand the nature of social studies for prospective teachers. The method used is Systematic Literature Review (SLR) by prioritizing the relevance of the theme of the previous article as the basis for data collection. Data analysis was carried out using interactive data analysis techniques. The results of the study indicate that it is very possible for a Bachelor of Social Studies Education to understand the nature of social studies during the study period if the social studies learning system can put an emphasis on integrated concepts and follow the existing social studies tradition. Discussion as a democratic step needs to be put forward to make students aware of the importance of learning social studies, so that the understanding that is built is not just normative, but what is expected is critical. The understanding that is built is based on the desire to ask and know, not unidirectional information given by the teacher or textbook. It is time for the field of social studies to be more open and democratic in shaping the character of teachers who understand the nature of social studies in supporting the ongoing development of national human resources.